EFISIENSI WAKTU, BIAYA TRANSPORTASI DAN TINGKAT KEMACETAN SEBELUM DAN SESUDAH ADANYA BUS TRANSJAKARTA KORIDOR 10 - Aang Gunawan (Institut Transportasi dan Logistik Trisakti, 2015)
TransJakarta BRT (Bus Rapid Transit) is expected by the government of DKI Jakarta to be the fast, safe, comfortable, reliable and reachable public transportation. This regulation is highly expected to impact on decreasing the traffic jam in Jakarta. The purpose of the study is to find out the efficiency and effectiveness of TransJakarta route 10, PGC Cililitan – Tanjung Priok Terminal (19, 4 km), in giving solutions to traffic jam especially in the rush hours. Based on the result, there is no significance differences in the cost of the trip before and after the TransJakarta route 10 opened. The only difference happens to the time used. Before the Transjakarta, the time used for reaching Tanjung Priok Terminal was 50, 74 minutes. But, after the government provides TransJakarta, Jakartans can get there in 40, 18 minutes. The speed of TransJakarta is 27 to 48 km/hour which is more efficient than the other public transportations (28.98 km/hour). 71, 43 respondents stated that the comfort of TransJakarta is good and 78, 57 respondents said that the safety is also good.